Antimicrobial Potential of the Yellow Plum (Ximenia americana): A Qualitative Evaluation of Ethyl Acetate Extracts from the Various Plants’ Parts - Bitrus, Solomon; Shoge, Mansurat O.; Agbo, Boniface O.; Moses, Simon; Shehu, Genesis Moses (Journal of Science Research and Reviews, 2025)
Medicinal plants have long been traditionally used as remedies for various ailments which include antimicrobials. Ximenia americana which belongs to the Olacaceae family is one of the plants used in traditional medicine in Africa. This study was targeted at assessing qualitatively, the antimicrobial potential of the ethyl acetate extracts from the roots, stem bark and leaves of the plant at different concentrations on selected environmental and clinical samples of bacterial and fungal pathogens using standard susceptibility test procedures. Extracts from the roots, stem bark and leaves of the plant revealed the presence of some phytochemicals ranging from glycosides (saponins and flavonoids), polyphenolics (tannins and steroids) to alkaloids. Alkaloids, flavonoids and steroids were found to be present in the same intensity in all parts while the leaves contained alkaloids, tannins, flavonoids steroids and steroids at varying intensities. The highest susceptibility was recorded from the leaf extracts where three of the test bacterial pathogens (Salmonella sp, Shigella sp and Staphylococcus aureus) showed varying degrees of susceptibilities at 20mg/ml, 25mg/ml, 30mg/ml, 35mg/ml and 40mg/ml. Furthermore, Staphylococcus aureus within this category exhibited the highest zone of inhibition (ZI) of  12mm indicating an increase in the disc size of 8mm conforming with Gentamycin (10µg) and Erythromycin (10µg) used as controls from commercially available antibiotic multi disks with ZIs of S (12mm). This study further reveals that the root extracts of the plant had no inhibitory effects on Aspergillus niger, Aspergillus flavus and Candida albicans at concentrations of 20mg/ml. 25mg/ml, 30mg/ml, 35mg/ml and 40mg/m. This finding potentially reveals the suitability of X. americana plant to be harnessed for its antibacterial potential through a further quantitative, safe and efficient evaluation of the specific bioactive components of the plant parts responsible for each antimicrobial activity as indicated in this study.
Keywords: Extracts; Harness; Inhibition; Potential; Susceptibility; Bioactive